Physico-chemical characteristics of lake water in 14 Slovenian mountain lakes - Muri, Gregor (Acta chimica slovenica, 2004)
Basic physical and chemical characteristics of the water in 14 Slovenian mountain lakes were determined. Surface water was sampled once a year over three consecutive years (2000-2002). The influences of lake and catchment areaproperties on the measured parameters were studied. The lake's trophic status and size of catchment area were found to affect the water chemistry. Pearson correlation coefficients were calculated to identify the strength of relation between the variables.. The highest correlation was found among the alkalinity, calcium and conductivity. Cluster analysis was additionally performed to obtain natural groupings in the data. Finally, the condition of the lakes was assessed. Although the water quality has deteriorated in some lakes (especially in Jezero na Planini pri Jezeru), most of the lakes are still in a good condition.
Keywords: Ammonia; Amoniak; Analysis; Bicarbonates; Bikarbonati; Calcium; Cluster Analysis; Electric Conductivity; Električna prevodnost; fizikalne lastnosti; Fosfor; Fresh Water; Hydrogen-Ion Concentration; Kalcij; kemijske lastnosti; Kisik; Magnesium; Magnezij; Nitrates; Nitrati; Oxygen; pH; Phosphorus; Planinska jezera; Skupek, analiza; Sladka voda; Slovenia; Slovenija; visokogorska jezera; voda; Voda, onesnaževalci kemični; Water Pollutants, Chemical